High-dimensional optimal stopping in discrete time - Malvikko, Antti (fi=Turun yliopisto|en=University of Turku|, 2018)
In this thesis we treat the problem of discrete time optimal stopping in a high-dimensional setting. Moreover, we present a known simulation framework for a Markovian case. This method provides a lower bound on the value. We also show that the general problem has a dual, which provides an upper bound on the value. The finite sample performance of three simulation algorithms is demonstrated in the context of Bermudan option valuation.